DIAGNOSTIC AND PROGNOSTIC SIGNIFICANCE OF INTRATHECAL SYNTHESIS OF IMMUNOGLOBULIN FREE LIGHT CHAINS IN MULTIPLE SCLEROSIS - V. D. Nazarov; S. V. Lapin; E. A. Surkova; E. P. Evdoshenko; G. S. Makshakov; Areg A. Totolian (Медицинская иммунология, 2015)
Increased intrathecal synthesis and oligoclonal banding of immunoglobulins (Ig) in cerebrospinal fluid (CSF) are major immunological findings in multiple sclerosis. Free light chains are fragments of Ig molecules that are produced in parallel to oligoclonal Ig, and their production reflects total Ig synthesis within central nervous system. Assessment of intrathecal kappaand lambda free light chain production within CNS compartment will help to improve diagnosis and prediction of outcomes in multiple sclerosis. Concentrations of kappa and lambda free light chains and clonality of immunoglobulin pattern synthesis were studied in paired CSF and serum samples of 151 patients, including 92 patients with multiple sclerosis, and 33 patients with clinically isolated syndrome which later was transformed into the definite multiple sclerosis. A control group consisted of 26 patients with other inflammatory diseases of central nervous system. Several Ig parameters have been determined in the patients, i.e., Ig clonality in CSF; concentrations of free light chains (both kappaand lambda-) in CSF; as well as their indexes and ratios. It was established that synthesis of kappa free light chains were significantly elevated in patients with multiple sclerosis. Moreover, the amounts of free light Ig chains in patients with positive oligoclonality test were significantly higher than in cases without intrathecal oligoclonal synthesis. With respect to diagnostic significance, the kappa quotient proved the best available option for diagnosis of multiple sclerosis. Its combination with Ig oligoclonality assays caused a decrease in false-negative diagnostics by 42%. Diagnostic benefit of the kappa quotient could be also confirmed by the data of ROC analysis. Also concentration of lambda free light chains in cerebrospinal fluid showed a negative correlation with conversion terms of clinically isolated syndrome to evident multiple sclerosis. Therefore, the indexes of free Ig light chains enables more precise diagnostics, like as more efficient severity evaluation of multiple sclerosis.